077 'NeuroPodcases: a clinical neuroscience podcast' – a remote learning resource. Issue 6 (27th May 2022) - Bharambe, Viraj; Healy, Sarah; Mayer, Josie; Williamson, John
Abstract : Background: Remote learning resources, such as podcasts, have grown in popularity and are of increas- ing importance during the 2020 pandemic. Podcast benefits include; convenience, accessibility to global expertise; and can be a useful adjunct to in-person teaching or a 'flipped classroom' approach. Methods: We developed a case-based podcast covering topics across clinical neuroscience for medical students and doctors. 'NeuroPodcases' are freely available via a dedicated website (neuropodcases. co.uk), Spotify, Apple Podcasts and Soundcloud. To maintain quality, all podcasts are created with a Neurology trainee and Consultant. Results: Over 35 neuroscience podcasts have been recorded for undergraduates (Essentials) and graduates (Advanced). Many are enhanced with additional illustrations and videos. There have been over 2, 700 plays across 36 countries, from all habitable continents. Feedback from local undergraduates suggests the podcasts are a useful adjunct at a time of limited bedside teaching. During a 4 week placement, the majority of students listened to >5 podcasts with 100% of respondents saying it increased their confidence in neurology. Conclusions: Podcasts offer a global learning resource which is freely available and can support clinical learning outside traditional clinical education environments. NeuroPodcases is an example of their utility for clinical neuroscience education. virajbh@hotmail.com